The Influence of Soft Skills and Discipline on Employee Work Productivity at Bedrock Hotel Kuta Bali - Febri Rahmad Agung; Youmil Abrian (Journal of Multidimensional Management, 2025)
The hospitality sector is central to Bali’s tourism industry, where employee productivity directly impacts service quality and competitiveness. This study examines the influence of soft skills and work discipline on employee productivity at Bedrock Hotel Kuta Bali. Using a quantitative causal-associative approach, data were collected from all 55 employees through a validated Likert-scale questionnaire. Soft skills were assessed via communication, teamwork, and initiative indicators, while work discipline included punctuality, adherence to rules, and task consistency. Multiple linear regression analysis, preceded by classical assumption tests, revealed that both soft skills (β = 0.518, p < 0.05) and work discipline (β = 0.577, p < 0.05) significantly and positively affect productivity, jointly explaining 86.6% of its variance. These results highlight that non-technical competencies and behavioral discipline are equally critical for enhancing operational performance in hospitality. Practically, the findings recommend implementing structured training to improve problem-solving, conflict resolution, and teamwork, alongside clear policies that strengthen punctuality and procedural compliance. Theoretically, the study extends human capital perspectives by confirming the complementary role of soft skills and discipline in driving productivity in service-oriented contexts. Future research should incorporate leadership style, organizational culture, and technology adoption to enrich the productivity framework in hospitality operations.